Pyrochlore-structured Y2Ti2O7–2TiO2 composite thin films for photovoltaic applications - Munawar, Khadija; Mansoor, Muhammad Adil; Olmstead, Marilyn M.; Yusof, Farazila; Misran, Misni; Basirun, Wan Jefrey; Mazhar, Muhammad (Springer, 2019)
A titanium-based heterobimetallic single-source precursor [Y2Ti4(μ3-O)4(μ2-O)3(H2O)(TFA)8(THF)5].3(THF) (1) (where TFA = trifluoroacetato and THF = tetrahydrofuran) was successfully used to fabricate pyrochlore-structured Y2Ti2O7–2TiO2 composite thin films on fluorine-doped tin oxide (FTO) substrates using the aerosol-assisted chemical vapor deposition technique (AACVD). The precursor complex (1), isolated in crystalline form by reacting yttrium (III) acetate monohydrate with titanium (IV) isopropoxide and trifluroacetic acid in THF solution, was characterized by physicochemical methods such as melting point, microanalysis, FT-IR, 1H-NMR, thermogravimetric analyses (TGA/DTG), and single-crystal X-ray diffraction. Thin films prepared at 550 °C were investigated by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), field emission gun-scanning electron microscopy (FESEM), and energy-dispersive X-ray spectroscopy (EDX) which demonstrated the development of mesoporous structured microballs of Y2Ti2O7–2TiO2 with precise stoichiometry. The optical analysis showed that Y2Ti2O7–2TiO2 has a direct optical band gap of 1.8 eV. Photo-oxidation of water via Y2Ti2O7–2TiO2 thin films was carried out under simulated solar irradiation of AM 1.5 G (100 mW cm−2) using three-electrode photoelectrochemical cell in of in three separate 0.5 M electrolyte solutions of NaOH (pH = 13.5), Na2SO4 (pH = 7.2), and citrate buffer (pH = 4). A best photocurrent density of ~ 60 μA cm−2 at + 0.8 V vs. SCE was observed at pH of 13.5. These observations were further validated by electrochemical impedance spectroscopy (EIS) studies in terms of charge transportation and its recombination time. © 2019, Australian Ceramic Society.